2022
DOI: 10.1088/1755-1315/1038/1/012033
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of a water level sensor under various turbidity levels in lowland crop production systems

Abstract: The practice of alternate wetting and drying (AWD), a water-saving technology in lowland crop production systems, can be greatly facilitated using wireless water level sensors. However, these sensors generally work under clear water conditions. The sensitivity of these sensors to turbidity is important for accurate water level measurement and appropriate irrigation scheduling. This study evaluated the performance of a high-end water level sensor of the submersible pressure transducer type under various turbidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The technology shows good potential to reduce fertilizer use and nutrient loss in Philippine banana plantations. Finally,Pereira et al (2022) developed and tested submersible water level sensors for measuring ood height in lowland rice elds under alternate wetting and drying irrigation regimes. They found that sensor accuracy was signi cantly affected by water turbidity.…”
mentioning
confidence: 99%
“…The technology shows good potential to reduce fertilizer use and nutrient loss in Philippine banana plantations. Finally,Pereira et al (2022) developed and tested submersible water level sensors for measuring ood height in lowland rice elds under alternate wetting and drying irrigation regimes. They found that sensor accuracy was signi cantly affected by water turbidity.…”
mentioning
confidence: 99%
“…Nano fertilizers, such as FertiGroTM tested by Augustus and Domingo[32] on banana plants, demonstrated signi cantly improved plant growth with the slow-release property making it suitable for direct soil application, potentially reducing fertilizer use and nutrient loss. Pereira et al[31] contributed to the landscape by developing submersible water level sensors for measuring ood height in lowland rice elds, offering improved regulation of water usage in water-scarce regions and enhancing irrigation e ciency under alternate wetting and drying regimes.…”
mentioning
confidence: 99%